The Implications of the Recent Economic Crisis on Fertility in Greece - Kotzamanis, Byron; Kostaki, Anastasia (European Journal of Economics and Business Studies, 2023)
A systematic review of past economic recessions occurred in developed countries confirms that social and economic crises often have serious effects on fertility while, beyond national differentiations, these effects have certain characteristics, e. g. a weak effect on generational fertility;an postponement on the timing of first birth, closely related to a late marriage or union;a close relationship between unemployment and age-specific fertility. The sensitivity of fertility behavior to economic crises is less marked in countries with longstanding family policies and strong social security systems. The recent social and economic recession in Greece took place under different social conditions than many recessions in the past. More women than ever are participating in the labor market, most couples use reliable contraception that enables them to postpone childbearing, while social security and health costs are burdened from the rapidly expanding numbers of elderly. All these factors can affect reproductive decisions and potentially aggravate the negative effects of the recession on fertility. This work, using the latest available official data of Greece, provides an investigation of the impact of the current economic crisis on fertility levels, as well as the evolution of these levels through time.